The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1590/s0100-06831999000400013
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade do cacaueiro em função de características do solo: I. características químicas

Abstract: RESUMO Avaliaram-se as produtividades em sete anos (1989 a 1995) de 36 talhões de cacaueiros (Theobroma cacao L.) de uma propriedade no município de Itagibá, Bahia. As médias das três maiores (anos mais chuvosos) e das três menores (anos O and in KCl, organic carbon, total N, Al, Ca, Mg, P, K, Na, Cu, Zn, Mn, Fe, H + Al and the remaining P) inrelative to two depths (0-20 and 30-50 cm) of soils with different textures. Data obtained from routine analysis (pH, Ca, Mg, P and K), in 1995, were correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Fertilizer trials have been carried out in all cocoa producing countries. They have shown that good correlations exist between cocoa yields and soil nutrients levels, thus confi rming that the method is well adapted for cacao growing and production improvement (Appiah et al 2000 ;Wessel 1971 ;Ahenkorah et al 1987 ;Bénac and Dejardin 1970 ;Morais 1998 ;Ojeniyi et al 1982 ;Paviot 1977 ;Santana et al 1971 ;Souza Júnior et al 1999b ;Tossah et al 2006 ;Wyrley-Birch 1987 ).…”
Section: First Research Resultsmentioning
confidence: 94%
“…Fertilizer trials have been carried out in all cocoa producing countries. They have shown that good correlations exist between cocoa yields and soil nutrients levels, thus confi rming that the method is well adapted for cacao growing and production improvement (Appiah et al 2000 ;Wessel 1971 ;Ahenkorah et al 1987 ;Bénac and Dejardin 1970 ;Morais 1998 ;Ojeniyi et al 1982 ;Paviot 1977 ;Santana et al 1971 ;Souza Júnior et al 1999b ;Tossah et al 2006 ;Wyrley-Birch 1987 ).…”
Section: First Research Resultsmentioning
confidence: 94%
“…In the vegetative part of the plant, Cu participates in various physiological processes such as redox, respiration, carbohydrate distribution, fixing and reduction of N protein for metabolism and cell walls and nucleic acids (Marenco and Lopes, 2009). Cu deficiency has been reported in cacao plantations (Souza Júnior et al, 1999), denoting that this micronutrient is quite in demand by cacao trees in this region.…”
Section: Discussionmentioning
confidence: 93%
“…In 1995, 36 of these plots were selected for the development of a research project that studied the correlation between edaphic attributes and cacao productivity. There was a predominance of a single soil unit per plot and a wide diversity of soils between plots (Souza Júnior, Ker, et al., 1999; Souza Júnior, Mello, et al., 1999).…”
Section: Methodsmentioning
confidence: 99%
“…The edaphic attributes studied came from the original database (Souza Júnior, Ker, et al., 1999; Souza Júnior, Mello, et al., 1999), which can be subdivided into chemical, physical, and mineralogical attributes. Chemical attributes and granulometry (sand, silt, and clay) were determined in deformed composite samples of air‐dried fine soil from two soil layers: 0.0–0.2 m (surface layer) and 0.3–0.5 m (subsurface layer); the intermediate layer, 0.2–0.3 m, was discarded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation